Students as assessment partners: A collaborative, qualitative evaluation of the Guns on Campus course-based undergraduate research experience - McLean, Katherine; Penascino, Samantha; McCauley, Jazzmine; Russell, Rachel; Martinez-Pitre, Kerian; Bish, David; `Kruis, Nathan (International Journal for Students as Partners, 2022)
The Students-as-Partners (SaP) paradigm has been widely recognized for its enrichment of pedagogy and research, particularly in the scholarship of teaching and learning; in a time of acute disruption to higher education, the SaP model may further provide key insights into the adaptation of high impact teaching practices, although the changing conditions of partnership require close attention. This paper reports on the qualitative evaluation of a multi-campus, hybrid course-based undergraduate research experience (CURE) delivered in the first year of the COVID-19 pandemic. Analysis of student reflection data was conducted by a research team of two faculty and four CURE-student participants in a process informed by the Students-as-Partners model. In addition to identifying student-reported challenges, solutions, and educational benefits associated with a hybrid CURE, we reflect on both the unique opportunities, and difficulties, offered by student-faculty partnerships formed and conducted in a virtual meeting space.